Geometries from structurable algebras and inner ideals - Meulewaeter, Jeroen (My University, 2020)
Se estudian ciertos tipos de geometrias en algebras estructurables via sus ideales internos abelianos.
Keywords: Lie, Algebras de; Geometría; Lie structures